To Be Born Amid War Conflict: The Right to a Legal Identity in Ukraine (Studia Prawnicze / The Legal Studies, 2021)
Human rights are an integral part of an open society and a democratic state governed by the rule of law. Among them, the right to a legal identity occupies an important place, however, ensuring its proper implementation in today's difficult conditions of war conflicts has not been an easy task. Not surprisingly, the necessity to provide a legal identity for all, including birth registration, is among the global goals of sustainable development, as this helps a person`s recognition before the law and protection of their rights, any of which may be violated unnoticed (right to a health care, education and others). Proper registration of a person's death also ensures that the rights of that person's heirs can be exercised.In this article, we examine the Ukrainian experience when ensuring the right of a person to birth and death registration through special civil proceedings. In the conclusions we justify a new approach to protecting the right to a legal identity and the method of its implementation within court procedure, in particular, in military conflicts, residence or permanent stay in temporarily occupied territories, etc. territories in which there are no legitimate public authorities.